Field assessment of potential exposure of dogs to leptospirosis by measuring antibody titers in dogs: a multisite study in five geographic regions of the United States - Carithers, Doug; Loebach, Ed; Williams, Troy; Sponseller, Jerlyn; Schreibman, Andrew; Platts, Diane (Frontiers in Veterinary Science, 2024)
This prospective research survey was performed to assess the level of exposure to Leptospira in well-cared-for, unvaccinated dogs residing in five different geographies across the United States: South-Central (East Texas), New England, the Mid-Atlantic (North Carolina and Virginia), Midwest (Wisconsin/northern Illinois), and Southwest (southern California). Since these dogs were well-cared-for and never vaccinated against Leptospira, one would assume that the veterinarians or owners did not expect an exposure potential for these dogs. However, 11.6% of the 1345 dogs assessed had MAT titers against one or more serogroups of Leptospira. Seropositivity does not necessarily indicate that disease will result, nor is there assurance that a specific serovar is involved, however a MAT positive does provide a measure of potential exposure and clinical signs or a carrier-state could result from infection. In this survey it was demonstrated that dogs that were considered no-or low-risk, were seropositive at a rate approximately 10 times higher than nationwide seropositivity for heartworm disease in the US (capcvet.org, 2024).